Impact of Metarhizium sp. and Trichoderma sp. on Soil Fertility and Growth of Tomatoes (Solanum Lycopersicum L.) in Post-Mining Land - Sopialena, Sopialena; Mirza, Alexander; Nggudu, Maria Fatima (KnE Life Sciences, 2022)
Soil conditions in coal mining areas are generally poor in terms of nutrient availability, necessitating the addition of nutrients as well as microbial investment to improve aeration and increase nutrient availability for plants. This study examined the ability of the fungi Metarhizium sp. and Trichoderma sp. to increase tomato plant growth and yield, as well as the ability of these fungi to increase soil fertility in post-coal mining soil. The data were compiled using a completely randomized design with four replications, and the study used post-coal mining soil. Metarhizium sp. and Trichoderma sp. were used, with doses of 0 g, 3 g, and 5 g in each treatment. Plant height, number of branches, number of flowers, and fruit production were all evaluated as growth parameters. The data were analyzed using variance with a level of 5% using the least significant difference test. Increases were found in soil pH, C-organic, nitrogen, phosphorus, and potassium, resulting in an increase in soil fertility. Adding Metharizium sp. and Trichoderma sp. increased soil fertility, tomato plant growth, and production. Keywords: Metarhizium sp., Trichoderma sp., post-coal mining soil